2021
DOI: 10.1002/jsfa.11316
|View full text |Cite
|
Sign up to set email alerts
|

Application of X‐ray diffraction and energy dispersive spectroscopy in the isolation of sulfated polysaccharide from Porphyra haitanensis and its antioxidant capacity under in vitro digestion

Abstract: BACKGROUND:The separation and purification of Porphyra haitanensis polysaccharide (PHP), and the determination of changes in molecular weight (Mw) and antioxidant capacity after in vitro digestion, were undertaken. RESULTS: Analysis of two polysaccharide fractions (PHP0.5-1-UF and PHP1.0-1-UF) by various techniques showed that they were very pure sulfated polysaccharides without pigment or protein. PHP0.5-1-UF was filamentous or 'tape-like' sheets, whereas PHP1.0-1-UF had some filaments and large numbers of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…P. haitanensis polysaccharide was extracted according to the previous method. [ 15 ] M. auratus [license No. SCXK (Shanghai) 2017‐0008] were purchased from the Songjian Experimental Animal Farm (Songjiang District, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. haitanensis polysaccharide was extracted according to the previous method. [ 15 ] M. auratus [license No. SCXK (Shanghai) 2017‐0008] were purchased from the Songjian Experimental Animal Farm (Songjiang District, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…[14] Polysaccharide is the main component of P. haitanensis. In our previous study, we isolated two fractions from P. haitanensis polysaccharide (PHP) [15] and characterized them as sulfated galactan [16] and sulfated glucogalactan. [17] Owing to its structure, high sulfate content and other factors, PHP has a variety of biological activities, such as anti-oxidation, [18] immune regulation, [19,20] anti-tumor, [21,22] intestinal flora regulation, [23,24] and hypolipidemic [25] effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is known [23,43,[55][56][57][58][59] that sulfation of polysaccharides leads to greater amorphization of their structure. Thus, the data shown in Figure 6 are in good agreement with the literature.…”
Section: X-ray Diffractions Analysismentioning
confidence: 99%
“…In the process of sulfation, an increase in the amorphization of the initial xanthan structure was observed, which was manifested by a decrease in the intensity in X-ray diffraction patterns from 17° to 50° 2θ. It is known [23,43,[55][56][57][58][59] that sulfation of polysaccharides leads to greater amorphization of their structure. Thus, the data shown in Figure 6 are in good agreement with the literature.…”
Section: X-ray Diffractions Analysismentioning
confidence: 99%
“…12 P. haitanensis polysaccharides (PHPs) are mainly composed of alternating β-(1 → 3)-D-galactose and α-(1 → 4)-3,6-endoether-L-galactose units and a sulfated linear skeleton. 13 Numerous studies have demonstrated that PHPs have immunomodulatory, anticancer, 14 and anti-bacterial, [14][15][16] anti-tumor, 17 and antioxidant 15,18 activities. PHPs can protect against human colon cancer cells through cell cycle arrest and apoptosis without causing adverse effects in vitro.…”
Section: Introductionmentioning
confidence: 99%